2021
DOI: 10.5455/medarh.2021.75.35-40
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Sepsis Patients Admitted to the Intensive Care Unit: Experience of 100 Cases

Abstract: Introduction: The term sepsis has a deep root all over medical history. It defined by a many physician and myth such as Homer’s Iliad. Sepsis defined as a clinical syndrome as an outcome from both systemic inflammatory response syndrome and infection. It can complicate by disturb the function of the organ (severe sepsis) and shock (septic shock). Aim: Our study aims to recognize sepsis cases in Al-Sader Medical city during 2019 and evaluate the management’s management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Also, investments are moderate and therefore in-house analysis using SUPSETS seems manageable (Supplementary Table S7). With significantly high costs for a septic patient per day at ICU and more reliable results than blood culture (Figure 4), SUPSETS might be an attractive option with respect to cost savings [7,43].…”
Section: Discussionmentioning
confidence: 99%
“…Also, investments are moderate and therefore in-house analysis using SUPSETS seems manageable (Supplementary Table S7). With significantly high costs for a septic patient per day at ICU and more reliable results than blood culture (Figure 4), SUPSETS might be an attractive option with respect to cost savings [7,43].…”
Section: Discussionmentioning
confidence: 99%
“…One major factor affecting the LOS in the ICU is the severity of the patient's illness or condition upon admission. Studies have consistently shown that patients with critical conditions, such as sepsis, acute respiratory distress syndrome (ARDS), or those requiring mechanical ventilation tend to have more extended stays in the ICU [10]. This underscores the importance of early identification and management of the critically ill patients to potentially reduce their LOS.…”
Section: Introductionmentioning
confidence: 99%